All those exanthematous fevers are not COVID-19 - Jaseem Sirajudeen (14777839) (2021)
Fever with a rash is a common case scenario that clinicians encounter in their practice. The ubiquity of the presentation is proportional to the magnitude of the physician’s dilemma due to its numerous causes. The diagnosis varies from infectious diseases to non-infectious, life threatening diseases including the current COVID-19 pandemic. Here we present a case of a 31-year-old male, who presented to the Emergency Department with fever and rash and was initially diagnosed and managed as a case of COVID-19 which on further evaluation proved to be brucellosis. This is a case of brucellosis with cutaneous manifestations which had been masquerading as COVID-19. Other Information Published in: Avicenna License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/avi.2021.1